Evaluating Research and Community Service at Sekolah Indonesia Davao: An SDG-Based Performance Assessment - Nina Yulianti (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study evaluates the institutional accountability and performance of Sekolah Indonesia Davao (SID) by assessing the alignment of its research and community service with the United Nations Sustainable Development Goals (SDGs). It moves beyond descriptive mapping to provide an evidence-based assessment of how this strategic diaspora institution fulfills its educational and social mandates within a global sustainability framework. Methodology: Utilizing an evaluative mixed-methods design, this study employs bibliometric analysis and a scoping review to assess institutional output. Data from academic databases and official records were analyzed using an SDG-based performance framework. Documents were scrutinized not only for thematic content but as indicators of institutional accountability and adherence to international quality education standards. Main Findings: The assessment reveals a steady increase in institutional output, primarily demonstrating accountability in SDG 4 (Quality Education) and SDG 16 (Peace and Justice) through cultural diplomacy and identity preservation. however, the evaluation identifies significant performance gaps in SDG 2 (Zero Hunger) and SDG 3 (Good Health and Well-being). These findings provide critical empirical evidence for institutional audits and resource reallocation to improve multidimensional accountability. Novelty/Originality of this study: This research establishes a novel evaluative framework for assessing the accountability of overseas educational institutions through SDG integration. It shifts the discourse from administrative reporting to systematic performance evaluation. The study provides a replicable model for evidence-based assessment, offering a foundational dataset for policy-driven accountability measures in diaspora education systems and international school management.